A PULMONARY INFECTION CAUSED BY MYCOBACTERIUM PEREGRINUM- A CASE REPORT. - Tatina T. Todorova; Violina Kaludova; Gabriela Tsankova; Neli Ermenlieva (Peytchinski Publishing, 2015)
Mycobacterium peregrinum is a member of the group of rapidly growing Nontuberculous Mycobacteria (NTM). It can be found in high frequency in natural and laboratory environments and is considered to be uncommonrare pathogen for both immunocompetent and immunosuppressed individuals. Currently, pulmonary infections caused by Mycobacterium peregrinum are unusual and diagnosed only in limited number of cases. Here, we present a clinical case of elderly man (72 years) with 1 month history of non-specific respiratory symptomatic. The patient was without underlying immunosuppressive condition or lung disease. Chest X-ray demonstrated persistent pleural effusion, opacities and cavitations in the right lobe. One of the sputum culturesgrewa rapidly growing mycobacterium and the isolated strain was found to be Mycobacterium peregrinumas identified by molecular genetic detection (PCR and DNA strip technology). To our knowledge, this is the third case in the world to report Mycobacterium peregrinumas a possible causative agent of pulmonary infection.